Recent Insights into Cellular and Molecular Mechanisms of Defective Angiogenesis in Systemic Sclerosis - Eloisa Romano; Irene Rosa; Bianca Saveria Fioretto; Mirko Manetti (Biomedicines, 2024)
In systemic sclerosis (SSc, or scleroderma), defective angiogenesis, clinically manifesting with abnormal capillary architecture and severe capillary reduction, represents a hallmark of early-stage disease, usually preceding the onset of tissue fibrosis, and is caused by several cellular and molecular mechanisms affecting microvascular endothelial cells with different outcomes. Indeed, once damaged, endothelial cells can be dysfunctionally activated, thus becoming unable to undergo angiogenesis and promoting perivascular inflammation. They can also undergo apoptosis, transdifferentiate into profibrotic myofibroblasts, or acquire a senescence-associated secretory phenotype characterized by the release of exosomes and several profibrotic and proinflammatory mediators. In this narrative review, we aimed to give a comprehensive overview of recent studies dealing with the cellular and molecular mechanisms underlying SSc defective angiogenesis and the related endothelial cell dysfunctions, mainly the endothelial-to-mesenchymal transition process. We also discussed potential novel vascular treatment strategies able to restore the angiogenic process and reduce the endothelial-to-mesenchymal transition in this complex disease.